Introduction of cloud computing technologies into the educational process of higher maritime educational institutions - O. O. Dobroshtan (Academy of Cognitive and Natural Sciences, 2013)
According to the Law of Ukraine "About the bases of development of information society in Ukraine for 2007-2015" one of the priority directions of state policy is the development of information society in Ukraine and implementation of the newest information and communication technologies in all spheres of social life. The use of the newest information and communication technologies, mobile services and World Wide Web in the educational process of the higher school was a necessary condition for the training of a competent specialist and his successful realization as a navigator in the conditions of informatization of society. At a time when purchase and maintenance of modern powerful equipment and software requires significant financial expenses for higher education institution, cloud computing becomes a worthy alternative.